Certain Considerations Regarding the Protection of a Capable Natural Person through Guardianship in the Light of New Romanian Civil Code - CREÈš, Daniela Cristina; BOBAR, Cosmina Flavia (Journal of Legal Studies, 2016)
One of the measures employed to protect an individual is guardianship. Legal norms treat guardianship aimed at protecting a person with full capacity of exercise in certain special situations in a different way than they do guardianship for minors or persons placed under interdiction. While guardianship for capable persons is governed by the rules of mandate, guardianship for minors and persons placed under judicial interdiction are subject to rules applicable to custody for minors (art. 171 of the New Civil Code). As follows, we shall analyse the legal provisions established by the New Civil Code in the case of guardianship for capable persons, emphasising novelty elements as compared to the previous regulation.